Cervical Spine Trauma Management - Rully Hanafi Dahlan; Sevline Estethia Ompusunggu; Farid Yudoyono (Indoscholar, 2018)
The incidence of spine injury following accidents are still very high in developing countries. Many problems occur after the accident including primary intervention on the scene, transportation to the public primary hospital, the referral system, and finally, the management at the central hospital. Cervical spinal cord injuries represent 20-33% of total spinal injuries with the prevalence of the subaxial levels. In patients with a preoperative neurological deficit due to spine trauma, in case of spinal cord compression or instability, surgery is often the treatment of choice to grant a chance of neurological recovery, early mobilization, and faster return to usual daily activities compared to the conservative treatment. In the past, many authors suggested a delayed surgical treatment to reduce postoperative complications rate, but recent studies have shown that an early decompression (< 72 h) may facilitate a postoperative neurological improvement probably due to the prevention of the secondary mechanisms of damage in acute SCI. In the context of the advanced management of spinal injuries, the main points of the focused assessment, the important waypoints of a full classification of the skeletal and spinal cord injury, the principles of early prioritization and decision making, the outline of the surgical strategy including indications, timing, approaches, technique and post-operative care, and the outline principles of rehabilitation. The authors in this paper try to summarize and create a guideline of management, based on experience in a regional centre.